Duration of Contact on Pulmonary Tb Transmission: Case Study - Control - Bellytra Talarima (Newinera Publisher, 2023)
The Ambon City Health Office, through the Prevention and Control of Infectious Diseases, pointed out that the number of new TB cases in Ambon City in the last three years has tended to increase, where in 2020 the number of cases was 716, in 2021 there were 961 and in 2022 there were 1,296 sufferers. with the number of deaths of 32 people in 2020, in 2022 and 2023 each of 23 people. This study used an analytic observational study with a case control study design, designed to determine the risk and the effect of exposure duration on pulmonary TB transmission with a total sample of 72, bivariate analysis using the chi square test and calculating the odds ratio (OR). multivariate analysis using binary logistic regression test. The results of the study found that close contact is a risk factor for TB transmission with OR = 4.857; contact time is a risk factor for TB transmission with OR = 6.143; and length of contact are risk factors for TB transmission with OR = 5.857. The binary logistic regression equation shows that someone who lives in the same house with a patient with pulmonary tuberculosis, exposure time > 8 hours/day and contact duration > 6 months, has a probability of suffering from pulmonary TB by 30% compared to someone without risk factors. In conclusion, the closeness of contact, contact time and duration of contact are risk factors for pulmonary TB transmission.